Inspiratory Muscle Training after Heart Valve Replacement Surgery Improves Inspiratory Muscle Strength, Lung Function, and Functional Capacity: A RANDOMIZED CONTROLLED TRIAL - Cargnin C. (2019)
Copyright © 2019 Wolters Kluwer Health, Inc. All rights reserved.Purpose: The aim of this study was to analyze the effects of inspiratory muscle training (IMT) as a therapeutic strategy after heart valve replacement surgery (HVRS). Methods: A double-blind, randomized, clinical trial that included patients undergoing elective HVRS, without post-operative complications, were allocated to 2 groups: IMT group (IMT-G) and IMT placebo group (IMT-PG). The IMT started 3 d after surgery and was performed twice daily for 4 wk. Lung function, maximum inspiratory pressure (MIP) as a measure of inspiratory muscle strength, functional capacity, and quality of life were assessed pre-operatively and at the end of training. Results: The IMT-G recovered pre-operative MIP and lung function values after 4 wk of training. This group also increased the distance walked during the 6-min walk test (6MWD). In the IMT-PG, the values of MIP were below those found pre-operatively, with impairment of lung function and lower 6MWD in the final evaluation. At the end of IMT, MIP was correlated with the 6MWD and with the spirometry variables. Conclusions: IMT performed for 4 wk after HVRS was effective in restoring the values of inspiratory muscle strength and lung function to the pre-operative level and increasing the functional capacity assessed by the 6MWD. Furthermore, an association between lung function and functional capacity was observed, demonstrating the clinical relevance of the use of IMT in the rehabilitation process of these patients.